Formulación y elaboración de una bebida isotónica utilizando diferentes concentraciones de (sacarosa, cloruro de sodio, citrato de sodio y citrato de potasio) a partir de jugo natural de naranja - Molina Pérez, Wendy Maribel (2021)
In this research work, a formulation and preparation of an isotonic drink using different concentrations of (sucrose, sodium chloride, sodium citrate and potassium citrate) from natural orange juice was carried out. To make this drink, several treatments were carried out with different concentrations of sucrose and salts. This isotonic drink contains water, carbohydrates and electrolytes in appropriate concentrations to restore the energy lost during physical activity; moreover, it has an osmolality equivalent to that of blood (isotonicity) to achieve an optimal speed of absorption in the intestine. For its formulation, it is recommended to use salts in adequate percentages as established by the Colombian Technical Standard (NTC) 3837 and thus reach the osmolality between 200 and 420 mOsm/L established by the same. Once the formulations were determined, 3 samples of the beverage were taken to determine the best treatment, all samples contained 75% of natural juice, which differed in sucrose and salts (sodium chloride, sodium citrate and potassium citrate), CarboxyMethylCellulose (CMC) was used as stabilizer and sodium benzoate as preservative. In addition, the samples were subjected to a previous pasteurization at 60°C for a period of 20 minutes for subsequent packaging in 500ml polyethylene containers and were kept refrigerated and at room temperature. The osmolality analysis of the samples was carried out, where positive results were obtained and the best treatment T2 was determined, corresponding to the formulation with (sucrose 6%, sodium chloride 0.064%, sodium citrate 0.040% and potassium citrate 0.026%, giving an osmolality of 309.75mOsm/L). The beverage was subjected to a physicochemical analysis, where the following results were obtained: 12 mEq/L sodium, 3.5 mEq/L potassium, 2.2 mEq/L calcium and 0.9 mEq/L magnesium. Coli and Total Coliforms such results are <10 CFU/mL and nutritional with 0% saturated fatty acids, 0% cholesterol, 11% sodium, 6% carbohydrates, 7% fiber, 20g sugars, 2% protein, vitamin C 94.5%, vitamin B3 30% and vitamin B6 45%. This isotonic drink has great sources of energy and electrolytes necessary for the body to rehydrate itself and sugars important for diabetics were identified.